Analyzing the Role of Women in Indian Politics and Its Implications for Gender Equality - Ahmad Parry, Suheel; Ahmad Bhat, Aaqib (International Journal of Psychosocial Rehabilitation, 2019)
This paper aims to analyze the role of women in Indian politics and its implications for gender equality. Despite the constitutional provisions and affirmative action policies, women’s participation in politics remains limited in India. This paper examines the factors affecting women’s political participation, the challenges faced by women politicians, and the initiatives taken by the government and civil society to enhance women’s political empowerment. The study also explores the impact of women’s political participation on gender equality and social development in India. Through an analysis of existing literature and empirical data, this paper argues that enhancing women’s political participation is crucial for promoting gender equality and social justice in India. The findings of this study have important policy implications for enhancing women’s political empowerment and promoting gender equality in India and other developing countries.